A prescrição intercorrente no direito tributário - Lattanzi, Sérgio Igor (2009)
This paper aims at consolidating the understanding of the possible application of the institute of the intercurrent prescription in tributary judiciary and administrative lawsuits. The basic support for our conclusions will be the prescribed constitutional foundations (principles) that will reinforce the possible application of the institute. We shall demonstrate the position of our courts concerning the subject, and we shall comment on the afore-mentioned decisions, which will make the reader to thing the theme over. We shall find discordant positions both in jurisprudence and doctrine, but we shall try to clear up eventual divergences with the principles of deontic logic, particularly the one concerning non-contradiction. We shall se that from the beginning the tendency of different cultures and countries has been not to eternalize legal relationships. Thus, leaving from this viewpoint we shall reach the conclusion that there is a possibility of application of the intercurrent prescription found both in the legal lawsuit (a long-established matter in our Courts) and in the administrative process (a matter not yet accepted by our Courts). Nonetheless, some of the reasons leading the Judiciary Power to understand the application of the intercurrent prescription in a lawsuit can be used to support its application in an administrative lawsuit. We shall present the most recurrent doctrines involving the subject, regardless of the scarcity of works on the matter concerning its application in tributary law, and we shall also propose a few solutions all through our paper. Finally, we shall make it clear that our paper does not intend to present definitive solutions, but simply to lead readers to consider the theme from a serious viewpoint. We see this paper as a guide for further discussions, and any suggestions will certainly be most welcome